2022
DOI: 10.1371/journal.pone.0263978
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of varying levels of soil salinity on emergence, growth and biochemical attributes of four Moringa oleifera landraces

Abstract: Salinity in soil and water is one of the environmental factors that severely hinder the crop growth and production particularly in arid and semi-arid regions. A pot experiment was conducted to investigate the impact of salinity levels (1.5 dS m-1, 3.5 dS m-1, 7.5 dS m-1 and 11.5 dS m-1) on emergence, growth and biochemical traits of moringa landraces under completely randomized design having three replications. Four landraces of Moringa oleifera (Faisalabad black seeded moringa [MFB], Patoki black seeded morin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
3
9
0
Order By: Relevance
“…Salt stress negatively correlated with growth parameters such as plant height, accumulation and allocation of fresh and dry biomass, and number of leaves (Fig. 1 , 2 ), which was in line with the previously reported data 71 , 72 . In contrast, salinity increased the root/ shoot fresh mass ratio, tissue density, and biomass allocation to root.…”
Section: Discussionsupporting
confidence: 92%
“…Salt stress negatively correlated with growth parameters such as plant height, accumulation and allocation of fresh and dry biomass, and number of leaves (Fig. 1 , 2 ), which was in line with the previously reported data 71 , 72 . In contrast, salinity increased the root/ shoot fresh mass ratio, tissue density, and biomass allocation to root.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results have been observed in previous studies of Elhindi et al (2016);; Sofy et al (2020) and Ren et al (2020). Also, Farooq et al (2022) revealed that all salinity levels significantly affected the germination and growth parameters of M. oleifera landraces. Soliman et al (2015) pointed out that salinity levels reduced growth parameters and chlorophyll content in M. peregrina.…”
Section: Discussionsupporting
confidence: 91%
“…All salinity levels significantly affected the emergence parameters of moringa landraces. Higher salinity levels significantly reduced root length, seedling length as well as seedling fresh and dry weights (Farooq et al, 2022).…”
Section: Introductionmentioning
confidence: 95%
“…For instance, if the concentration of the ions in the soil increases through a salinity increase, the crop productivity may be limited because of poisoning and possible plant death [ 48 ]. Moreover, it may lower the seedling growth rate, resulting in a decrease in crop productivity because of a decreased soil water potential [ 49 , 50 ]. Therefore, the limited salt variability in the results can be interpreted as a potential positive factor in agricultural production.…”
Section: Resultsmentioning
confidence: 99%